The role of placement instability on employment and educational outcomes among adolescents leaving care. (December 2021) - Goyette, Martin; Blanchet, Alexandre; Esposito, Tonino; Delaye, Ashleigh
Highlights: We use data from interviews with 1136 youth transitioning out of Quebec 's care system. The data is supplemented by information from the administrative records of all youth. Placement instability is linked to much higher probability to drop out of school early. Instability is related to a higher probability not to be acquiring work experience. Instability is associated with lower probabilities to receive a high school degree. Abstract: Placement instability negatively impacts the lives of youth placed in out-of-home care, and research on the topic indicates that it is related to negative long-term outcomes for youth in care. This study uses information gathered from two waves of interviews conducted with a representative sample of 1136 Quebec youths who were first met at around 16 years of age when they were still in out of home placement, and at around age 18 when most of them had left placement. The youths' associated administrative child welfare data were also used to examine the relationships between placement instability, education outcomes, and occupational status. We find that youth who experience more placement instability have a much higher probability of dropping out of school early, and not to be acquiring work experience. Our results also indicated that these youths have a much lower probability to receive a high school degree.